The Role of Students’ Emotions in Foreign Language Achievements among Iranian EFL Learners in Yazd - Esmaeei Ranjbar Jamal Abadi; Farideh Sadat Sajjadipour; Fatemeh Yavari (Iranian Evolutionary Educational Psychology Journal, 2025)
Objective: The emotional landscape of language learning has garnered increasing scholarly attention in recent years, particularly as researchers recognize the profound impact of affective variables on second language acquisition (SLA). This study investigates the effects of three key learner emotions-foreign language enjoyment (FLE), foreign language classroom anxiety (FLCA), and foreign language learning boredom (FLLB)-on English language achievement among junior secondary school students in Yazd, Iran. Methods: The sample comprises 300 Iranian EFL learners aged 12–15, attending junior secondary schools in Yazd. Participants were surveyed at four intervals across a nine-week term using validated scales: the Foreign Language Classroom Anxiety Scale (FLCAS), the Foreign Language Enjoyment Scale (FLES), and the Foreign Language Learning Boredom Scale (FLLBS). Results: The study finds that FLE positively predicts English achievement, while FLCA and FLLB have negative effects. FLE emerged as the most enduring predictor over time, highlighting the value of positive emotions in sustaining language learning outcomes. Conclusions: Implications for pedagogy and curriculum design are discussed, and recommendations for future research in Iranian schools are provided.